Emotions and involvement in tourism settings. Issue 10 (19th May 2022) - Santos, Vasco; Sousa, Bruno; Ramos, Paulo; Valeri, Marco
ABSTRACT: This paper aims to present an extensive content analysis of two major constructs directly related to tourist behaviours (i.e. involvement and emotions), because there are still some critical gaps in the knowledge about tourists' emotions and involvement. An in-depth content analysis of involvement and emotions was adopted as a methodological approach. To address the content analysis, a set of papers published in renowned scientific databases, such as Science Direct, Web of Science, Scopus, Emerald, Taylor and Francis, Elsevier, Sage and Wiley were selected and analysed. The major findings state that emotions and involvement demonstrate greater progress and scientific development to the level of tourism, marketing and consumer behaviour, representing an important issue for the integrated tourism experiences. Future studies should analyse and evaluate the role and impact of emotions and involvement in post-pandemic contexts. Hence, there is a growing potential for managers and stakeholders to achieve the benefits derived from the study outcomes.